Soft skills among students: a case study of UiTM Cawangan Kelantan / Muhammad Faizal Samat, Norazlan Annual and Raznee Atisya Md Rashidi - Samat, Muhammad Faizal; Annual, Norazlan; Md Rashidi, Raznee Atisya (Universiti Teknologi MARA, Shah Alam, 2019)
This article contributes to ongoing debates about soft skills among students. In 2017, the unemployment rate in Malaysia was at 3.42 percent as compared to 2.85 percent in 2014. Education system must aim towards employability and ensure quality in education to reduce the percentage of unemployment. Thus, this study aims to investigate the development of soft skills among students through co-curriculum activities in UiTM Cawangan Kelantan. The sample were 113 students from UiTM Cawangan Kelantan. Questionnaires adapted from previous research to measure the communication skill, problem solving skill, team building skill, leadership skill and soft development of soft skills among students through co-curriculum activities. SEM-PLS 3.0 were employed in this study. The findings revealed only team building skill has significant influence on developments of soft skills among students through co-curriculum activities. However, the study indicates that communication skill, problem solving skill and leadership skill are not significant towards development of soft skills among students through cocurriculum activities.